ISOLASI DAN IDENTIFIKASI KAPANG ENDOFIT DARI Avicennia marina (Forssk.) Vierh. - Efrita Bataragoa; Susi Kusumaningrum (ADISAM PUBLISHER, 2023)
Endophytic fungi are microorganisms that live symbiotically with plant tissue. In general endophytic fungi capable to producing secondary metabolite compounds similar to their host and has various potential biological activities. The goals of this research is to identify the endophytic fungi species of the Avicennia Marina (Forssk.) Vierh. This research was conducted through the isolation from leaf, twig and root of Avicennia Marina (Forssk.) Vierh. on PDA (potato dextrose agar). There are 8 isolates of endophytic fungi achieved from isolation with diverse genera: Arthrinium, Aspergillus and Phomopsis